SEGMENTING THE U.S.A. NON-TRAVEL MARKET - Wayne W. Smith; Emily Fralinger; Stephen W. Litvin (Enlightening Tourism: A Pathmaking Journal)
Tourism marketers focus on understanding the many different segments that comprise their visitors.  Understanding these segments’ motivations for travel is important in order to motivate repeat visitation and to attract like-minded consumers to visit.  But how about those who do not travel?  This surprisingly large percentage of the population is a lost opportunity for the industry.  The research that follows, based upon a very significant USA-based sample of non-travelers, suggests that non-travelers can be effectively segmented and targeted. Understanding these segments will better allow vacation marketers to craft their product and their message, hopefully bringing more travelers to the mix.